PENERAPAN STRATEGI PEMBELAJARAN PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 008 TELUK PULAU HULU - Samsimar, Samsimar; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study is based on the low learning outcomes of science students of fourth grade SD Negeri 008 Teluk Pulau Hulu Academic Year 2016/2017. Preliminary data received by the researchers, from 28 students who reached the value of KKM only 8 students (26.67%). This research is an Action Research Classroom which is done collaboratively and participatively in collaboration with science teacher of class IV in SD Negeri 008 Teluk Pulau Hulu. The instrument of this research consists of learning device used in this research based on Education Unit Level Curriculum (KTSP). Learning tools consist of syllabus, lesson plans, student worksheets and observation sheets. The result of research got the activity of teacher of first meeting of cycle I that is 60% with enough category, second cycle meeting to I that is 70,83% with good category. At siklu II meeting 1 that is 79,17% with good category and second meeting second cycle that is 91,67% with very good category. Then the first activity percentage of first cycle students is 54,17% with enough category, at second meeting of cycle I that is 70,83% with good category. In the second cycle of meeting I is 83.33 with very good category, and meeting II is 87,5 with very good category. Student completeness also increases. In the preliminary data The number of completed students before the action was held was only 7 students (25%) with an average score of 64.5. In the daily re-test I completed the students to 13 students or (46.43%) with an average score of 75.2. Furthermore, in the second cycle II repetition increased again with the total number of students who complete 25 students or (89.28%) with an average score of 83.93. This means that the classical value obtained by students has been above the established KKM.Keywords: Concept Map Strategy, Learning Outcomes IPA